Trace Amine-Associated Receptor 1 Modulates the Locomotor and Sensitization Effects of Nicotine - Sukhanov, Ilya; Dorofeikova, Mariia; Dolgorukova, Antonina; Dorotenko, Artem; Gainetdinov, Raul R. (Frontiers in Pharmacology, 2018)
Trace amine-associated receptor 1 (TAAR1) has emerged as a promising target for addiction treatments because it affects dopamine transmission in the mesolimbic pathway. TAAR1 is involved in the effects of addictive drugs, such as amphetamines, cocaine and ethanol, but the impact of TAAR1 on the effects of nicotine, the psychoactive drug responsible for the development and maintenance of tobacco smoking, has not yet been studied. This study was performed to investigate the possible modulatory action of TAAR1 on the effects of nicotine on locomotor behaviours in rats and mice. Pretreatment with the TAAR1 agonist RO5263397 dose-dependently decreased nicotine-induced hyperlocomotion in rats habituated to locomotor boxes, prevented the development of nicotine sensitization and blocked hypermotility in nicotine-sensitized rats at the highest tested dose (10 mg/kg). The lack of TAAR1 failed to affect the effects of nicotine on the locomotion of mutant mice. Based on the results of the present study, TAAR1 activation attenuates the locomotion-stimulating effects of nicotine on rats. These results further support the previously proposed hypothesis that TAAR1 is a promising target for the prevention and treatment of drug addiction. Further studies aimed at analyzing the effects of TAAR1 agonists on animal models of nicotine addiction are warranted.